Vitamin D3 alleviates high-fat induced hepatopancreas lipid accumulation and inflammation by activating AMPKkα/PINK1/Parkin-mediated mitophagy in Litopenaeus vannamei - Tianmeng Dai; Jingjing Lu; Xinyue Tao; Xin Zhang; Ming Li; Min Jin; Peng Sun; Weijin Liu; Lefei Jiao; Qicun Zhou (Aquaculture Reports, 2022)
A high-fat diet (HFD) model was built to elucidate the regulatory mechanisms of vitamin D on lipid metabolism in shrimp. An 8-week feeding trial was aimed to determine whether dietary vitamin D3 would ameliorate the adverse effects of HFD feeding in Litopenaeus vannamei. A total of 360 shrimp (initial weight of 0.50 ± 0.01 g) were randomly divided into three diets with three replicates, and each replication consisted of 40 shrimp. Three experimental diets included the control diet (NFD, 7.36% fat, 45.71% protein), HFD (11.32% fat, 45.89% protein) and the HFD supplemented with 0.57 mg/kg vitamin D3 (HFD+VD). The results revealed that growth performance was not affected (P > 0.05) by different experimental diets in L. vannamei. Compared with the control group, HFD group significantly increased (P < 0.05) serum low-density lipoprotein, cholesterol, triglyceride and hepatopancreas lipid accumulation (confirmed by genes expression, morphology observation and fatty acid composition) in L. vannamei. Hepatopancreas inflammation related gene (tnf-α, rab6a) levels and damaged mitochondria numbers were significantly increased (P < 0.05), while levels of immune related genes (alp, acp, lzm) and mitophagy related genes (ampkα, pink1, parkin, atg13, atg14, atg16, atg101) were decreased (P < 0.05) in L. vannamei. Compared with the HFD group, HFD+VD group significantly decreased (P < 0.05) hepatopancreas lipid deposition in L. vannamei. Hepatopancreas inflammation related genes (tnf-α, aif, rab6a) levels and damaged mitochondria numbers were significantly decreased (P < 0.05), while mitophagy related genes (ampkα, pink1, parkin, becline, atg13, atg14, atg16, atg101, atg9, atg12, lc3) and immune related genes (alp, acp, lzm) were increased (P < 0.05) in L. vannamei. In conclusion, the results of present study showed that: (1) High fat diet could promote hepatopancreas lipid accumulation, increase inflammation and inhibit mitophagy in L.vannamei; (2) Dietary vitamin D3 supplementation could alleviate high-fat induced hepatopancreas lipid accumulation and inflammation by activating AMPKkα/PINK1/Parkin-mediated mitophagy in L.vannamei.